The Justification of Tyrannicide in the Chronicle of Dalimil. The Czech Nobility as the “Mystical Body” of the Realm - Éloïse Adde (Medievalista)
The chronicle of the so-called Dalimil is the first chronicle written in the Czech language, dating from the early 14th century. In the context of the succession crisis (interregnum of 1306-1310) entailed by the death of Venceslas III, murdered without descent, and the extinction of the Přemyslide dynasty, its author’s plane was to establish the political role of the Czech nobility. Next to the emphasis on the election of the ruler by the Lords, the justification of the tyrannicide had to play a crucial role. In front of a king who could be weak (Henry of Carinthie), foreign (John the Blind) or too young (Venceslas II at the beginning of his reign), the nobility had to embody the durability of the State, the "community of the realm", in a dialectic that connected the Lords in the idea of constituting the "mystic body of king". In this text, the necessity of the application of the tyrannicide is not however presented as a novelty, but as a fundamental and almost moral duty of the nobility, which was abandoned because of the rise of the authoritarian exercise of the power by the ruler when the duchy of Bohemia became a Kingdom.